2017
DOI: 10.1021/acsmedchemlett.7b00168
|View full text |Cite
|
Sign up to set email alerts
|

Development of Potent Myostatin Inhibitory Peptides through Hydrophobic Residue-Directed Structural Modification

Abstract: Myostatin, a negative regulator of skeletal muscle growth, is a promising target for treating muscle atrophic disorders. Recently, we discovered a minimal myostatin inhibitor (WRQNTRYSRIEAIKIQILSKLRL-amide) derived from positions 21-43 of the mouse myostatin prodomain. We previously identified key residues (N-terminal Trp, rodent-specific Tyr, and all aliphatic amino acids) required for effective inhibition through structure-activity relationship (SAR) studies based on and characterized a 3-fold more potent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Therefore, we examined the in vivo efficacy of E31R in mdx mice (5-week-old male) through histological analysis based on hematoxylin and eosin staining using a previously reported procedure. 21 As shown in Figure S1, intramuscularly injected E31R, compared to saline, induced an increase of gastrocnemius (GAS) muscle fiber sizes. Additionally, peptides 3 and E31R similarly increased GAS muscle fiber sizes in wild-type C57BL/6 mice compared to saline ( Figure S2).…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 90%
See 3 more Smart Citations
“…Therefore, we examined the in vivo efficacy of E31R in mdx mice (5-week-old male) through histological analysis based on hematoxylin and eosin staining using a previously reported procedure. 21 As shown in Figure S1, intramuscularly injected E31R, compared to saline, induced an increase of gastrocnemius (GAS) muscle fiber sizes. Additionally, peptides 3 and E31R similarly increased GAS muscle fiber sizes in wild-type C57BL/6 mice compared to saline ( Figure S2).…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 90%
“…These results suggested that the myostatin inhibitory activity of peptide 4a is attributed to the adequate hydrophobic interaction derived from its β-sheet structure, predominantly formed by amino acid substitutions at positions 32 and 38, which is a similar case previously observed in peptide 3. 21 Compared with peptide 4a, other inhibitory peptides 4b, 5, 6, and 8a exhibited even higher content of the β-sheet structure along with their enhanced inhibitory activity ( Figure 5). In particular, the content of the most potent peptide 8a was 76%.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 96%
See 2 more Smart Citations
“…Different strategies are currently in preclinical and clinical investigation. They comprise drug candidates specifically targeting the cytokine such as anti‐myostatin antibodies, peptibodies, adnectin‐ and follistatin‐Fc fusion proteins, and agents derived from the myostatin propeptide, as well as multi‐target approaches such as receptor competitors and anti‐ActRII antibodies . Domagrozumab (PF‐06252616; Pfizer, New York City, NY) is a humanized monoclonal anti‐myostatin antibody developed for the treatment of Duchenne muscular dystrophy, which prevents receptor activation through binding to the circulating cytokine .…”
Section: Introductionmentioning
confidence: 99%